Deja-Vu : The Cimarron News-Press, January 12, 1907 (Cimarron, New Mexico Cimarron Legend, 1992)
Article on editorials of yesteryear. This particular article is on the Cimarron news-press in 1907 about cleaning up Cimarron, New Mexico.
Master List Item # 25
File location is in the New Mexico File Cabinets
Keywords: Town Clean up; Trash; Community; Cimarron, New Mexico